On a Fluid Outflow from a Bottle Turned Upside-Down - Skakauskas, V.; Katauskis, P.; Simeonov, G. (Nonlinear Analysis: Modelling and Control, 2006)
An incompressible viscous as well as nonviscous fluid outflow from an axially symmetric bottle turned upside-down is considered. This problem relates the gravity acceleration and air bubbles inflow into the bottle and in the mathematical sense presents a very complicated task. The simplified setting of problem based on a one-dimensional approximation of the fluid flow is proposed and results of numerical experiments are discussed.